SISTEM PENJADWALAN MENGAJAR DI SMA NU AL MA’RUF KUDUS MENGGUNAKAN ALGORITMA GENETIKA - Nor Wahyono; Agus Subhan Akbar; Joko Minardi (Universitas Islam Nahdlatul Ulama Jepara, 2022)
At SMA NU Al Ma'ruf Kudus, the management of the teacher's teaching schedule related to rooms andclasses still use conventional or manual methods and have not fully use computerized processing. Problems thatarise in the beginning of each learning year is the occurrence of a schedule that collides with several studentsteacher. Starting from the background of the existing problems, the author designed the System Web-basedinformation to be implemented for scheduling processing teaching at the NU Al Ma'ruf Kudus High School. In thisstudy, the Genetic Algorithm method used to build a scheduling information system by completing complexoptimization problems, which are difficult to perform by conventional methods. Results research shows that theGenetic Algorithm method can be used to build a teaching scheduling system. By generating a different task_IDconsists of subjects and teachers to produce the best fitness values in the shortest time short. From testing bygenerating as many as 10 chromosomes and 25 generations the best fitness value = 0.024, time = 126.99seconds, in the 12th generation.